Compression testing of martensitic stainless steel with superimposed ultrasonic vibration - Michalski, Markus; Piott, Florian; Merklein, Marion (Procedia Engineering, 2017)
LFT Import::2019-07-29 (2233)
Keywords: Finite element method (FEM); high strength steel; metal forming; ultrasonic

Dynamic correction of oscillatory forces during ultrasonic-assisted metal forming - Michalski, Markus; Leicht, Uwe; Heath, Andrew; Merklein, Marion (Production Engineering, 2017)
Numerous investigations in the past decades reported that the forces required for forming processes can be reduced by superimposing high frequency oscillation. Even though many studies have been carried out identifying and assessing the complex cause of this reduction, cause-effect relationships are generally not yet established in detail. Since the measurement of dynamic forces plays a key role in clarifying the causes, a precise measurement of the forming forces oscillating with high frequency is necessary. Although dynamic force measurement is a well-known field of research, this study focuses on its utilisation for ultrasonic-assisted forming processes. Since dynamic effects distort original measurements in this frequency range, adjustment is required. Based on measurement instruments with high temporal resolution the present study introduces an approach for creating and employing a frequency dependent force correction in the high dynamic range. The experimental procedure for creating a transfer function up to a limiting frequency of 40 kHz is later analysed and verified by numerical modal and transient simulations. The results indicate that the highly location dependent dynamic force detection has major influence on peak forces. Observed deviations can be precisely corrected using the generated frequency dependent transfer function.
LFT Import::2019-07-29 (2239)
Keywords: Finite element method (FEM); Force; Measurement; Metal forming; Transfer function; Ultrasonic

Grundlegende Untersuchungen zum Prozess- und Werkstoffverhalten bei schwingungsüberlagerter Umformung - Michalski, Markus (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
The superposition of mechanical tool vibrations with frequencies in the ultrasonic range is an approach that enables a considerable reduction of forming forces. So far, however, the incomplete understanding of the detailed process behaviour constrains the technologies broad industrial application. The central purposes of this thesis are the identification of responsible mechanisms for the phenomenon of vibration-based softening and the investigation of the ultrasonic influence on material forming limits. Metallic materials of four different classes are tested: martensitic stainless steel X17CrNi16-2, mild steel S235JR, wrought aluminium AW-6082 T6 and cast aluminium AC-43400. Apart from the known effect of vibration-induced force reduction, substantial specimen heating was recorded in a fundamental process analysis. In addition, a strongly altered forming behaviour was observed. Thermal softening and material-related influences have been identified as crucial mechanisms regarding force reduction. With respect to the forming limits of metallic materials under the influence of ultrasonic vibration, a significant reduction was found for all investigated materials. For the practical application of the technology, this implies potentials concerning reduced tool and workpiece loading as well as a more flexible press selection. This applies in particular to less critical forming operations regarding material failur

Hall measurement method for the detection of material defects in plastic-embedded permanent magnets of rotors - Brela, Matthäus; Michalski, Markus; Gebhardt, Hans Joerg; Franke, Jörg (IECON Proceedings (Industrial Electronics Conference), 2013)
The efficiency of electric drives is determined by the mechanical and magnetic properties of the functional elements, such as stator and rotor. Due to the electromagnetic interaction with the magnetic field, generated by the stator, the rotor transforms the magnetic energy into a rotational motion. It is characterized by its magnetization, its magnetic field strength, the field distribution and its geometric dimensions. The current challenge is to produce electrical drives with minimal loss. This requires ensuring the magnetic characteristics of the rotors. Errors that can occur during manufacture are cracks, blowholes or inclusions in the permanent magnet. Those can lead to commutation problems or to increased noise. For this purpose, a non-destructive and non-contact measurement method, based on the measurement of the magnetic field with Hall-effect sensors to detect defects in plastic-bonded permanent magnet rotors was developed. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuators and System Integration; Diagnostic and Prognostic; Fault Detection; Permanent Magnet Machines; Sensors

Influence of ultrasonic vibration on the shear formability of metallic materials - Michalski, Markus; Lechner, Michael; Gruber, Micha; Merklein, Marion (CIRP Annals - Manufacturing Technology, 2018)
The flow stress reduction of metallic materials due to superimposed ultrasonic vibration is an intensively researched phenomenon. So far, however, only a few studies have analysed the vibrational influence on forming limits. Existing findings are inconsistent, suggesting both a formability extension and a decrease. Ultrasonic-assisted shear tests constitute a novel experimental approach for the fundamental investigation of predominant cause–effect–relationships. The test results reveal a distinct correlation between the application of ultrasonic vibration and earlier material failure. This effect is attributed to enhanced crack initiation and propagation caused by localised stress and strain concentration as well as intermittent high strain rates.
LFT Import::2019-07-29 (2298)
Keywords: Failure; Forming; Ultrasonic

Residual effects of ultrasonic-assisted compression testing on pure copper - Jäckisch, Manuel; Michalski, Markus; Merklein, Marion (AIP Conference Proceedings, 2019)
Due to the rising demand for weight and volume reduction, the usage of high strength materials becomes more and more common. Regarding process forces, the application range of existing presses is limited in forming such metals. One approach to reduce the process forces considerably is superimposing the tool movement with ultrasonic vibration. Although the immediate occurring force and mean stress reduction were first discovered in 1955 by Langenecker and Blaha and are known phenomena, underlying effects of ultrasonic-based material softening remain object of current research. Prominent theories explaining the acoustic softening are stress superposition as well as surface and volume effects. By carrying out ultrasonic-assisted compression tests with 20 kHz oscillation frequency on pure copper, this study intends to determine permanently altered material characteristics. Therefore, compression testing with varying oscillation interval as well as amplitude is conducted and force-displacement-curves are analyzed. In comparison to conventional upsetting, an initial softening effect occurs after the unique presence of ultrasonic-assistance. Moreover, metallographic analyses support former findings. With regard to the examination of material flow as well as grain deformation, permanent microstructure alteration is found. In this way, temporary process-related and permanent material-induced effects are separated.
CRIS-Team Scopus Importer:2019-07-23

Tool Load Sensitivity against Multidimensional Process Influences in Microblanking of Thin Metal Foils with Silicon Punches - Hildering, Sven; Michalski, Markus; Engel, Ulf; Merklein, Marion (Journal of Manufacturing Science and Engineering, 2016)
LFT Import::2019-07-29 (2169)

Tool System for Ultrasonic-Assisted Forming and Material Characterisation with 15 kHz Oscillation Frequency - Michalski, Markus; Leicht, Uwe; Engler, S.; Merklein, Marion (Applied Mechanics and Materials, 2015)
LFT Import::2019-07-29 (2102)

Ultraschallunterstütztes Umformen und Verstemmen - Aktuelle Ergebnisse aus dem Verbundprojekt "UltraCaulk" - Leicht, U.; Michalski, Markus; Merklein, Marion (wt Werkstattstechnik - Online, 2017)
Substantial force reductions can be achieved by superimposing high frequency oscillation on forming processes. The joint research project UltraCaulk focusses on fundamental investigations on the material flow behaviour during ultrasonic influence and the transferability of identified mechanisms on industrial caulking processes. This study analyses the influence of process parameters on the resulting force reduction and specimen heating.
LFT Import::2019-07-29 (2199)

Ultraschallunterstützte Umformung von Metallen - Entwicklung eines Prüfstands zur Werkstoffcharakterisierung mit 15 kHz Schwingungsüberlagerung - Michalski, Markus; Merklein, Marion (wt Werkstattstechnik - Online, 2015)
LFT Import::2019-07-29 (2120)

Ultrasonic-Assisted Upsetting of Steel with 15 kHz Oscillation Frequency - Michalski, Markus; Merklein, Marion (Key Engineering Materials, 2016)
LFT Import::2019-07-29 (2170)
Keywords: Cold Forming; Metal; Ultrasonic